The Differences of career self-efficacy in the selection of careers among Malay students at International Islamic University Malaysia - Ismail, Zuraidah (Educational Research Association, Turkey, 2010)
This study was conducted to examine the link between career self-efficacy and career selections of university students. The study was also aimed to find out the differences of career self-efficacy in terms of gender and socio-economic status. The study was restricted to Malay students, and Malay is one of the main races in Malaysia. Participants selected for this study were undergraduate Malay students from different faculties at International Islamic University, Malaysia. The number of samples selected was 200, consisting of 100 males and 100 females. The instrument used in the study was designed by Bentz and Hackett (1981) and was adapted by the researcher to suit the Malaysian context. Data was analyzed using t-test and one-way variance. The result indicates significant differences in career self-efficacy in successfully completing the educational requirements and performing job duties of traditional and nontraditional careers with regard to gender. The result of this study also indicates that female students show higher career-self-efficacy for both traditional and non-traditional careers,compared to male students. The study also shows that students from high economic status reported higher career self-efficacy compared to students from medium and low socio economicstatus. Key words